2013
DOI: 10.1093/bja/aet076
|View full text |Cite
|
Sign up to set email alerts
|

Is thoracic ultrasound a viable alternative to conventional imaging in the critical care setting?

Abstract: Thoracic imaging is regularly performed on the majority of critical care patients. Conventionally, this uses a combination of plain radiography and computed tomography. There is growing enthusiasm for the use of ultrasound to replace much of this radiology and provide more immediate, point-of-care imaging with reduction in patient transfers, ionizing radiation exposure and cost. This article explores the diagnostic performance of thoracic ultrasound in the imaging of pleural effusion, consolidation, extra-vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 52 publications
2
23
0
2
Order By: Relevance
“…Of interest, we found a higher incidence of atelectasis and pleural effusions detected by lung ultrasound in these patients. This finding could be explained by the higher sensitivity and specificity of lung ultrasound in detecting pleural effusion and atelectasis compared with CXR, when compared with the gold standard for thoracic imaging, computed tomography (CT) scans . Furthermore, our results are comparable with the reported incidence of atelectasis of 90% found with thoracic CT scan in anaesthetised patients .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Of interest, we found a higher incidence of atelectasis and pleural effusions detected by lung ultrasound in these patients. This finding could be explained by the higher sensitivity and specificity of lung ultrasound in detecting pleural effusion and atelectasis compared with CXR, when compared with the gold standard for thoracic imaging, computed tomography (CT) scans . Furthermore, our results are comparable with the reported incidence of atelectasis of 90% found with thoracic CT scan in anaesthetised patients .…”
Section: Discussionsupporting
confidence: 79%
“…Cardiac ultrasound has been shown to be valuable in the peri‐operative assessment and therapeutic management of patients undergoing surgery . In non‐cardiothoracic surgery patients, lung ultrasound performed better than CXR in diagnosing pneumonia, pulmonary oedema, pneumothorax and pleural effusion . Until now, however, there have been limited data available for the diagnostic value of lung ultrasound in cardiothoracic surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lung ultrasound has been proven to be almost as accurate as CT scanning in detecting the presence of pneu-mothorax [4] occult pneumothorax and its extension [5]. In the present study and after analyzing 49 patients (64 hemothoraces) we found that ultrasound had a sensitivity of 92.8%, a specificity of 87.5%, a positive predictive value of 98.1%, and a negative predictive value of 63.6%.…”
Section: Discussionsupporting
confidence: 52%
“…Among methods for detecting atelectasis, lung ultrasound is a fast, simple, non‐invasive and radiation‐free technique which has gained increasing popularity, especially in emergency and critical care settings . Furthermore, lung ultrasound has shown reliable sensitivity and specificity for the diagnosis of anaesthesia‐induced atelectasis in children .…”
Section: Introductionmentioning
confidence: 99%